The use of topical sodium hypochlorite in the management of Pseudomonas aeruginosa burn wound infection - Coetzee, Emile (Department of Surgery, 2014)
The aim of the study is: 1. To undertake a meta-analysis of Pseudomonas aeruginosa burn wound infection. 2. To undertake a retrospective audit of Pseudomonas aeruginosa burn wound infection at the Red Cross War Memorial Children's Hospital. 3. To investigate the local effects of sodium hypochlorite solutions in Pseudomonas aeruginosa burn wound infection with regards to efficacy and toxicity.